2020
DOI: 10.3390/ijms21207440
|View full text |Cite
|
Sign up to set email alerts
|

Offensive Behavior, Striatal Glutamate Metabolites, and Limbic–Hypothalamic–Pituitary–Adrenal Responses to Stress in Chronic Anxiety

Abstract: Variations in anxiety-related behavior are associated with individual allostatic set-points in chronically stressed rats. Actively offensive rats with the externalizing indicators of sniffling and climbing the stimulus and material tearing during 10 days of predator scent stress had reduced plasma corticosterone, increased striatal glutamate metabolites, and increased adrenal 11-dehydrocorticosterone content compared to passively defensive rats with the internalizing indicators of freezing and grooming, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 62 publications
0
20
0
6
Order By: Relevance
“…The mechanism of the moderating role of glutamate within the limbic stress system circuits is largely unknown, however, lower glutamate levels in the amygdala of more active subjects seems to be associated with less anxiety and decreased plasma cortisol (CORT) levels ( 3 ). On the other hand, lower glutamate levels in the striatum were associated with lower adrenal 11-dehydrocorticosterone and higher plasma CORT ( 5 ). These inverse reaction patterns of the limbic Glu-Cort circuits could be explained by the paradigms of caco- and hyper-stasis ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the moderating role of glutamate within the limbic stress system circuits is largely unknown, however, lower glutamate levels in the amygdala of more active subjects seems to be associated with less anxiety and decreased plasma cortisol (CORT) levels ( 3 ). On the other hand, lower glutamate levels in the striatum were associated with lower adrenal 11-dehydrocorticosterone and higher plasma CORT ( 5 ). These inverse reaction patterns of the limbic Glu-Cort circuits could be explained by the paradigms of caco- and hyper-stasis ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that obese humans, labeled as low cortisol reactors, consume less food, and that more active and “offensive” rats have low levels of anxiety and increased glutamate+glutamine levels in the striatum and inversely related glutamate levels in the amygdala ( 3 5 ). These pathophysiological limbic circuit changes are present not only in patients with obesity and/or less physical activity, but also in patients with PTSD ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we previously reported that chronic predator scent stress (PSS)-induced PTSD was accompanied by adrenal damage, especially in the GC-producing zona fasciculata, as well as plasma corticosterone (CORT) reduction [8]. Moreover, we found inverse CORT levels in high-vs. low-anxiety allostatic flight/fight/active (AFR) or allostatic freezing/passive (APR) responders to chronic stress [9]. However, no histomorphological data related to CORT reduction in chronically stressed subjects are available.…”
Section: Introductionmentioning
confidence: 99%
“…Converging evidence suggests that the striatum as one of the important neural substrates is disturbed in the reward circuitry of depression and anxiety by stress ( Admon et al, 2015 ; Ullmann et al, 2020 ; Martin-Soelch et al, 2021 ). In the present work, the striatal site-specific proteomic signatures of the three stressed and Ctrl groups were comparatively determined through the use of an iTRAQ-based quantitation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Striatal dopamine D2/3 receptor-mediated neurotransmission is also reported to be involved in the pathophysiology of anxiety and depression ( Schneier et al, 2008 ; Nikolaus et al, 2010 ; Leggio et al, 2015 ; Admon et al, 2017 ; Peciña et al, 2017 ). The striatum may be a structure in which stress and reward processing interact ( Admon et al, 2015 ; Ullmann et al, 2020 ). Specifically, stress, on the other hand, reduces the activation of the striatum in response to reward and elicits robust dopamine release in the striatum on the other ( Martin-Soelch et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%